The overstory : [large type] a novel - Powers, Richard, 1957- (Thorndike Press large print core series., 2022)
An Air Force loadmaster in the Vietnam War is shot out of the sky, then saved by falling into a banyan. An artist inherits a hundred years of photographic portraits, all of the same doomed American chestnut. A hard-partying undergraduate in the late 1980s electrocutes herself, dies and is sent back into life by creatures of air and light. A hearing- and speech-impaired scientist discovers that trees are communicating with one another. These four, and five other strangers, each summoned in different ways by trees, are brought together in a last and violent stand to save the continent's few remaining acres of virgin forest.